SOME ASPECTS OF THE ATMOSPHERIC ELECTRIC CLIMATE AT IBADAN (1980)
The diurnal variations of the atmospheric electric Parameters and meteorological Parameters for the harmattan season of November 1978 to March 1979 are presented. The percentage variations of temperature are mirror images of those of vapour pressure which show pronounced depressions around noon when the little available moisture in the air near the ground is distributed over greater and greater heights by convection. The diurnal patterns of dust concentration, measured for the first time in this locality, is single periodic with minimum between 0400 hrs and 0800 hrs L.T. and maximum around 20 hrs L.T. This pattern is closely related to that of windspeed, and is explained in terms of the copious amount of dust transported southwards from the Sahara desert. The diurnal curves of the electric elements. I, H and p show pronounced “austausch” depressions around noon and marked peaks at 08.00 hrs which are attributable to the sunrise effect. An average value of the total nuclei concentration during the Harmattan months is computed to be about 2.8x10(10) particles per m(3) for this Station. This value is based on the measurements of the polar conductivities made for the first time in Ibadan.